PEMELIHARAAN POST LARVA (PL4-PL9) UDANG VANNAMEI (Penaeus vannamei) DI HATCHERY PT. BANGGAI SENTRAL SHRIMP PROVINSI SULAWESI TENGAH - Kalesaran, Ockstan J (Sam Ratulangi University, 2010)
White shrimp culture have been developed in some part of brackish water pond area in Indonesia, either in extensive, semi intensive or intensive technology and it resulted increasing on Indonesian shrimp culture production. Â At post larval stages, the pleopods become fully developed and functional. The animals grow very fast in terms of size and are able to swim freely although early post larvae are still planktonic. This research was done to know post larval rearing in Hatchery of PT. Banggai Sentral Shrimp. Preparation of basic facilities such as larval rearing tanks, water supply and aeration system is one of the most important activities in hatchery operation. Â Good water quality should be strictly maintained especially during this phase of larva rearing.